Not by adding 1, but just working the equation like 0 is a variable.

02 ¹ 0 and 3 * 0 ¹ 0

02 0 and 3 * 0 0 are computational operations not mathematical operations.

02 and 3 * 0 in an equation, the 0 is a variable and needs to be handled through mathematical equation solving operations not computational operations.]]>

.

.

.

Now, the tricky math part.

Using the values of MIN, MAX, SUM, and PRODUCT we can find the values of X_LOW and X_HIGH.

Taking the SUM of W, X, Y, and Z, if we subtract the values of MIN and MAX we are left with the sum of the two middle numbers X_LOW and X_HIGH.

Sum of X_LOW and X_HIGH: n = SUM - MIN - MAX

Taking the PRODUCT of W, X, Y, and Z, if we]]>

The place to discuss the strong ties between lotteries and mathematics.

Excuse me, but I think I'm missing the strong tie between lotteries and mathematics in this thread.]]>

I know how to add, subtract and multiply.

I think.]]>

1 - If X / X = 1, then - / - = 1

- / - = 1

- = 1 * -

- = - , true \ - / - = 1

2 - If X / X ¹ 1, then - / - ¹ 1

- / - ¹ 1

- ¹ 1 * -

- ¹ - , false \ - / - = 1

3 - If X / X = 1, then 0 / 0 = 1

0 / 0 = 1

0 = 1 * 0

0 = 0, true \ 0 / 0 = 1

4 - If X / X ¹ 1, then 0 / 0 ¹... [ More ]]]>

n =

( n ) / = /

n ( / ) = /

n ( 1 ) = 1

n = 1, \ n = true when n = 1

n ¹

( n ) / ¹ /

n ( / ) ¹ /

n ( 1 ) ¹ 1

n ¹ 1, \ n ¹ true when n ¹ 1

n = -

( n ) / = - /

n ( / ) = - /

n ( 1 ) = -1

n = -1, \ n = - true when n = -1 <--- correction from previous post

n ¹ -

( n]]>

0 * = n

( 0 * ) / = n /

0 ( / ) = n /

0 ( 1 ) = n /

0 = n / , if and only if n = 0 *

0 * = n

( 0 * ) / 0 = n / 0

( 0 / 0 ) = n / 0

( 1 ) = n / 0

= n / 0

= n / 0 , if and only if n = 0]]>

n =

( n ) / = /

n ( / ) = /

n ( 1 ) = 1

n = 1, \ n = true when n = 1

n ¹

( n ) / ¹ /

n ( / ) ¹ /

n ( 1 ) ¹ 1

n ¹ 1, \ n ¹ true when n ¹ 1

n = -

( n ) / = - /

n ( / ) = - /

n ( 1 ) = -1

n = -1, \ n = true when n = -1

n ¹ -

( n ) / ¹]]>

1 - If -1 = 0 , then 0 + -1 = 0

0 + -1 = 0

0 + ( 1 / ) = 0

0 ( / ) + ( 1 / ) = 0

( ( 0 * ) / ) + ( 1 / ) = 0

( 0 * + 1 ) / = 0

0 * + 1 = 0 *

( 0 * ) - ( 0 * ) + 1 = ( 0 * ) - ( 0 * )

0 + 1 = 0

1 = 0

1 = 0 , is false \ -1 ¹ 0

2 - If -1 > 0 , then 0 + -1 > 0

0]]>

1 - Reciprocal Operation with Inequality

a > b

taking the reciprocal of both side causes the > to change to <.

reciprocal of a > b is a-1 < b-1

a > ba-1 < b-1

aba-1b-1

10.251.000004.00000

10.51.000002.00000

210.500001.00000

21.50.500000.66667

1050.100000.20000

1090.100000.11111

10005000.001000.00200... [ More ]]]>

1. 0-1 = (1 / 0) = , is not correct

2. -1 = (1 / ) = 0 , is not correct]]>

4/4 = 1 3/3 = 1 2/2 = 1 1/1 = 1 0/0 = 1]]>